Agency Theory and Sustainability in the Global Supply Chain - Delbufalo, Emanuela (SpringerBriefs in Business,, 2018)
This book analyzes how and under what conditions collaborating corporations can effectively manage relationships with their suppliers in order to decrease the risk of suppliers' noncompliance with codes of conduct and standards. In so doing, it represents an important addition to the management literature on corporate social responsibility in global supply chains - which is highly topical at a time when companies are increasingly aware of the social and environmental aspects of global sourcing. After an opening systematic review of the literature on agency theory and supply chain management, it explores the rationale underlying collaboration among competitors, and the most critical aspects of such collaboration, in depth. Thanks to the book's use of real-life examples, readers will learn how agency theory can help improve relationship management and address the major issues in sustainable global sourcing.